Spain's grim lesson for British workers : manifesto of the Militant Labour League - Jackson, Starkey (London : Published for the M.L.L. for the Militant Publishing Association)
SA15-010-001 1 page SPANISH SUPPLEMENT. MILITANT. MARCH, 1939. Spain’s Grim Lesson For British Workers Manifesto of the Militant Labour League To-day, when the Spanish workers are facing defeat after over two-and-a-half years of bitter civil war, it is necessary for the workers of this country to learn from the experience of our Spanish comrades in order that they may not repeat their mistakes. The reasons for the defeat must be established and the responsibility placed where it belongs. It is an easy answer to lay the blame on Chamberlain and his non-intervention policy. But the Russian Revolution was successful against the armed intervention of all the western “democracies” as well as internal counter-revolution. The workers do not need and must not expect assistance from capitalist governments in their struggles. They need and must demand active solidarity and assistance from the working class in the rest of the world and a correct leadership at home. The rank and file workers throughout the world have shown their willingness to assist the Spanish workers in every way possible. Many have laid down their lives in the struggle, others have given money they needed themselves to buy food and clothing, they have raised their voices in protests against the infamous arms embargo. But for months the Second International supported non-intervention. The Labour Party leaders in this country supported it, and "socialist" premier Leon Blum refused to give the Spanish Government the right to buy arms which he now demands the reactionary Daladier Government give. The Soviet Union participated in the Non-Intervention Committee, thereby lending the prestige of the workers’ state to this farce. The Soviet Union also failed to give adequate material support to the Popular Front Government which they supported so strongly in words. In 1923, when there was the possibility of a workers’ revolution in Germany, the Red Army was massed on the borders in order that active support might be given, although the Soviet Union was weakened and disorganised by years of civil war and imperialist intervention. But now, when the Soviet Union is far stronger, when we are told that socialism is finally established, the Government of Stalin can afford only meagre shipments of arms and food. SECOND AND THIRD INTERNATIONALS FAIL. The Second and Third Internationals were united in their efforts to confine the struggle in Spain to one between democratic capitalism and fascist capitalism, although the whole of post-war history shows that it is impossible for capitalist democracy to be maintained in this period of decline of the whole of capitalist economy, that it is not a question of democracy or fascism but of socialism or fascism. The Second and Third Internationals have betrayed the workers of Spain. The collapse of the Popular Front in Spain coincides with the development of a campaign in its favour in this country. The British workers must not be deceived as were the Spanish workers. An alliance between the working class and capitalist parties means that the workers must confine themselves to a purely capitalist programme, for the capitalists will not accept a working class policy. It means that instead of fighting for the overthrow of the whole decaying system which brings unemployment, misery and war to the masses, the working class must limit its struggles to electing a coalition government, which, they hope will grant them a few reforms and keep fascism at bay. But experience has proved not only that the Popular Front cannot give anything but very small and temporary concessions to the workers, but that it paves the way for fascism in exactly the same way as the policy of the social democrats of Germany paved the way for Hitler. In Spain, the workers were not given better conditions, nor was the land given to the peasants, but that did not prevent Franco from rising to overthrow the Popular Front Government, and the workers were unprepared to meet his onslaught. In fact, the Government did everything in its power to lull the working class, to avoid giving them arms and to make an immediate peace with Franco. In France, the gains which the workers won in the June strikes were taken away by successive inflations, by compulsory arbitration, and finally by Daladier’s attacks on the forty-hour week. The Popular Front has brought into power a reactionary government under Daladier. The workers are no nearer their emancipation than they were before, and in addition they are disoriented and disillusioned by the class collaborationist policies of their leaders. A Popular Front in this country will result in the defeat and disillusionment of the workers and pave the way for fascism and war. The only progressive class to-day, the only class which can free the masses of humanity from poverty and exploitation, is the working class, and it can only fulfil its historic role through the overthrow of capitalism and the establishment of socialism. The class-collaboroation [collaboration] of the Popular Front and of the reformists is designed to bolster up the capitalist system. It is necessary for the working class to free itself from the pernicious influence of these traitors to the working class, to build a new, a revolutionary leadership both nationally and internationally, capable of leading them to the final victory — Socialism. Now more than ever must we build up the organisation of the revolutionary left in the Labour Party — the Militant Labour League. Only a revolutionary organisation based upon the principles of Marxism and intransigeant class struggle can lead the workers to victory. The Popular Front Leads To Fascism Spain’s agony reaches its climax. After 8 years of revolution and 32 months of civil war, the workers and peasants of Spain now fight with their backs to the wall. The workers of Britain must now learn the tragic lessons of their failure and defeat. The Spanish workers could have won; Fascism could have been defeated; Capitalism could have been overthrown and the power of the workers and peasants established. Since the monarchy was overthrown in 1931, the workers of Spain have demonstrated over and over again, their capacity for heroic struggle and sacrifice and their will to victory. The responsibility for the present situation, for the victory of fascism, rests not upon the heroic workers and peasants of Spain, but primarily and above all upon the treacherous policy and conduct of their leaders — the Socialists, Communists and Anarchists. The Popular Front was a guarantee of the victory of Fascism. Through the Popular Front the organisations of the working class became the hostages of Spanish capitalism. The whole policy of the Popular Front has been an attempt to win the support of the Spanish capitalists and the “Western democracies.” POPULAR FRONT TREACHERY To carry through this policy, it had to convince its prospective allies that it could maintain the power and property of Spanish capitalism without the aid of Fascism. For this reason it liquidated the social gains of the revolution, it handed back the property of the capitalists and the landowners, it refused the land to the peasants, it refused the factories to the workers, it refused the independence to the Moroccan people, it savagely suppressed revolutionary socialist elements, it liquidated the workers’ militia and in its stead created a new capitalist army. The Popular Front, fearful of rousing the revolutionary will of the Spanish workers and peasants, which alone could have won the war, even took steps to safeguard capitalist property in its continued retreats. Vast stores of material and vital factories were allowed to fall untouched into the hands of Fascism. To-day the workers and peasants of Spain gather the bitter fruits of this treachery. The Generals of the Popular Front army have taken the power out of the nerveless hands of the politicians and prepared to hand it to Franco. As we write, the workers are facing the firing squads in Madrid. Tragic irony that at the end of the magnificent 30 months defence of Madrid, its defenders are now being shot down, not by the Fascist Franco, but by the Generals of the democratic republic! By Miaja, whose portrait has been carried in innumerable Communists' processions all over the world. RANK AND FILE FIGHT BACK. We pay our tribute to the Communist workers of Madrid, who, deceived, betrayed and deserted by their leaders, made one last desperate effort to fight back. While the “Communist” ministers, the famous Passionaria and the rest of the cowardly crew saved their skins by flight abroad, their deluded followers fight on to the bitter end. The Popular Front, in spite of all its treachery, failed in its objective, as it was bound to fail. Spanish capitalism could not be convinced that anything but a Fascist dictatorship could keep the revolutionary spirit of the Spanish toilers in check. The Western powers were not prepared to risk a European war to defend “democracy” when they could assure themselves of the financial control of a Fascist Spain. Thus the whole flimsy fabric of the Popular Front is torn to shreds, and the “struggle between democracy and Fascism,” exposed as a myth. In the final line-up, Spanish capitalism, democratic and Fascist alike, unite against the common enemy — the workers and peasants. Having demoralised and confused the Spanish toilers, the Popular Front now hands them over to the Fascist executioners. The principle responsibility for the defeat in Spain rests upon the Communist International. The heroic combat of the Communist workers of Madrid cannot palliate this; on the contrary, it intensifies the guilt. COMMUNIST PARTY THE TRAITORS. The Spanish Communist Party leaders were the principle agents in the liquidation of the revolution; it is they who preached confidence and trust in the Popular Front Government and covered up its counter-revolutionary activities; it is they who [l]ed the murder campaign against the revolutionary socialists. It was the Communist International who drew the workers of other lands away from revolutionary intervention on behalf of their Spanish comrades and diverted them to the useful but entirely secondary task of collecting food and money. Instead of taking the lead for a general strike on an international scale to smash the arms embargo and the infamous non-intervention farce, it begged the “democratic” imperialists to do the job for them. In every single detail the Communist International has been proved to be an instrument of counter-revolution. Workers of Britain must learn the lessons of Spain. Only in this way can they avoid a repetition of the disastrous mistakes and defeats. These lessons can best be summed up in the words of the greatest revolutionary of our epoch:— "Promises are cheap; promises cost nothing. It is on promises that all the bourgeois politicians in all the bourgeois revolutions have been feeding people and fooling the workers. "'Our revolution is a bourgeois revolution, therefore the workers must support the bourgeoisie.' say the worthless politicians among the liquidataors [liquidators]. "'Our revolution is a bourgeois revolution,' say we Marxists, 'therefore the workers must open the eyes of the people to the deceptive practices of the bourgeois politicians, must teach the people not to believe in words, but to depend wholly on their own strength, on their own organisation, on their own unity, and on their own arms.' " (Lenin, "Letters from Afar," page 11). Through the observance of this advice the workers and peasants of Russia overthrew capitalism and seized the power, holding it against all comers. Through violating its principles the Spanish Popular Front led the workers and peasants to defeat. The workers of Britain, if they are to win through and avoid the horrors of Fascism, must base their policy and activity on the principles of Leninism, on the waging of the class struggle against capitalism, which is the cause of Fascism and war. Revolutionary class struggle leads to victory; class collaboration leads to fascism and disaster. STARKEY JACKSON. Published for the M.L.L. by the Militant Publishing Association, 12-14, Red Lion Court, Fleet Street. E.C.4 and printed by the Sydenham Press, Queensthorpe Road, S.E.26. 15X/1/173/2